2019
DOI: 10.1021/acs.biochem.9b00486
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Active Site Communication Mediated by the Dimer Interface β-Sheet in the Half-the-Sites Enzyme, Thymidylate Synthase

Abstract: Thymidylate synthase (TS) is a dimeric enzyme conserved in all life forms that exhibits the allosteric feature of half-the-sites activity. Neither the reason for, nor the mechanism of this phenomenon is understood. We used a combined NMR and molecular dynamics approach to study a stable intermediate preceding hydride transfer, which is the rate limiting, and half-the-sites step. In NMR titrations with ligands leading to this intermediate, we measured chemical shifts of the apo enzyme (lig 0), the saturated hol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 75 publications
(193 reference statements)
2
8
0
Order By: Relevance
“…The NMR titration experiments with the FdUMPCH 2 H 4 F diligand showed that allosteric changes accompanying diligand binding that may lead to half-of-the-sites reactivity are mostly transmitted through the β-sheet interface and involve changes to the dynamics of the two active sites. 16 Consistent with the NMR titration experiments, there are subtle differences in the strand containing active site nucleophile Cys146 in the inactive monomer B. In monomer B of both Int-B analog structures, the side chain of Phe149 in this strand is in two alternate conformations, and in the (6R)-Int-B analog, Cys146 and His147 both adopt alternate conformations (Figure S4).…”
supporting
confidence: 73%
See 1 more Smart Citation
“…The NMR titration experiments with the FdUMPCH 2 H 4 F diligand showed that allosteric changes accompanying diligand binding that may lead to half-of-the-sites reactivity are mostly transmitted through the β-sheet interface and involve changes to the dynamics of the two active sites. 16 Consistent with the NMR titration experiments, there are subtle differences in the strand containing active site nucleophile Cys146 in the inactive monomer B. In monomer B of both Int-B analog structures, the side chain of Phe149 in this strand is in two alternate conformations, and in the (6R)-Int-B analog, Cys146 and His147 both adopt alternate conformations (Figure S4).…”
supporting
confidence: 73%
“…There are also differences between the two protomers in the dynamics of the catalytic Cys146 and adjacent residues. The NMR titration experiments with the FdUMPCH 2 H 4 F diligand showed that allosteric changes accompanying diligand binding that may lead to half-of-the-sites reactivity are mostly transmitted through the β-sheet interface and involve changes to the dynamics of the two active sites . Consistent with the NMR titration experiments, there are subtle differences in the strand containing active site nucleophile Cys146 in the inactive monomer B.…”
supporting
confidence: 55%
“…Long-range H-bond networks also control the correlated motions among β-strands in β-sheet rich proteins. Such correlated motions respond to physical perturbations by controlling the extent and rate of elastic deformations in a protein 48,[56][57][58][59][60] . Proteins with stronger correlated motions can thus withstand larger perturbations.…”
Section: Proline Mutation Induces Weaker Correlated Motions In β-Strandsmentioning
confidence: 99%
“…The ligand-induced conformational change upon CHO-H 4 folate and its noncompetitive inhibition in the NADH:menadione oxidoreductase assay were unexpected, as the change in dimer interface (dimer mode 1) is less extensive (than dimer mode 2); crystallographic evidence shows that CHO-H 4 folate is found only in the active site. Several other folate-binding enzymes, namely DHFR ( 18 ) and TYMS ( 31 , 32 ), have shown that protein motions, in the form of conformational sampling in the active site (DHFR) or the existence of conformational ensembles (both) are crucial not only to catalysis but represent a route through which allostery can emerge. In the case of TYMS, the existence of a ligand-induced β-kink in the dimer interface directly couples the active sites between monomers and explains its observed half-sites reactivity ( 31 ), with an asymmetric dimer assembly structure elucidated ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several other folate-binding enzymes, namely DHFR ( 18 ) and TYMS ( 31 , 32 ), have shown that protein motions, in the form of conformational sampling in the active site (DHFR) or the existence of conformational ensembles (both) are crucial not only to catalysis but represent a route through which allostery can emerge. In the case of TYMS, the existence of a ligand-induced β-kink in the dimer interface directly couples the active sites between monomers and explains its observed half-sites reactivity ( 31 ), with an asymmetric dimer assembly structure elucidated ( 32 ). More studies are necessary to determine how noncompetitive inhibition in tMTHFR occurs and could prove invaluable in delineating the catalytic cycle of MTHFR itself.…”
Section: Discussionmentioning
confidence: 99%